Covariates of Currently Married Women's Employment in Nepal: A Regional Analysis - Kafle, Ramesh Babu (Journal of Management and Development Studies, 2015)
This paper studies regional differences in currently married women’s employment status, its nature and some of the covariates in Nepal, with special focus to their education and economic status by analysing data from Nepal Demographic and Health Survey, 2011. Women’s employment, with substantial regional variation in the three ecological regions, is predominately unpaid, done mainly for family members, mostly in agriculture sector and women work throughout the year. Women are employed mainly in family farm and their job is unpaid. Higher education of women is positively associated with their involvement in paid jobs. Women of better wealth strata are less likely to be employed but if employed, they are more likely to be in paid jobs. Increasing education of women may have mixed effect in future. Policy measures are desirable to minimize these regional differences and to reallocate the total labour force in general and the female labour force in particular in more productive sectors with secured paid jobs for women for prosperity of the country.